E-Supply Chain Management Value Concept for The Palm Oil Industry - Muhamad Akbar; Antoni Darius (Jurnal Sistem Informasi, 2019)
The Harmony of IT and Business is an asset and the foundation of the organizations to improve and build business competitive strategies. There is a need to integrate and coordinate all business partners of the organization, particularly those associated with Information Technology and suppliers, raw materials or resources needed in the supply chain management. The effectiveness of an E-SCM in Palm Oil industry will be the crucial factor to provide the organization with business opportunities and improve competitive position in the marketplace. Aim of this study is to investigates critical factors E -Supply Chain Management in Oil Palm Industry through Theory Resource Based View (RBV). With RBV theory, this study develops a concept that can be utilized for identifying the critical success factors of E-SCM value in Palm Oil industry. The quantitative research method is used for collecting data in four Palm Oil organizations in South Sumatera. This research reveals that IT human resources and IT infrastructure are the critical factors and capability in to operate E-SCM effectively and